Factor XII Defect and Hemorrhage Evidence for a New Type of Hereditary Hemostatic Disorder - Egeberg, O (Thrombosis and Haemostasis, 1970)
In some members of 4 Norwegian families, a slight to moderate bleeding tendency was found to be associated with a partial blood factor XII defect, the factor activity about half of average normal level. In keeping with the low factor XII, surface activation rate of factor VII in plasma was found significantly decreased.The disorder seems to be transmitted as an autosomal intermediately dominant trait.A high incidence of cerebral apoplexy was recorded in the patients, and the first cerebrovascular attack had in most affected patients occurred at a relatively early age.In some of the patients attacks of localized edema, severe headache and abdominal pain, and different types of allergy remind of the problems of the demonstrated non-coagulation properties of factor XII.The results are discussed.